ARCHITECTING SOLUTIONS WITH SAP BUSINESS TECHNOLOGY PLATFORM an architectural guide to integrating and extending enterprise solutions using SAP BTP - Simsekler, Serdar (PACKT PUBLISHING LIMITED, 2022)
A practical handbook packed with expert advice on architectural considerations for designing solutions using SAP BTP to drive digital innovation Purchase of the print or Kindle book includes a free eBook in the PDF format Key Features Guide your customers with proven architectural strategies and considerations on SAP BTP Tackle challenges in building process and data integration across complex and hybrid landscapes Discover SAP BTP services, including visualizations, practical business scenarios, and more Book Description SAP BTP is the foundation of SAP's intelligent and sustainable enterprise vision for its customers. It's efficient, agile, and an enabler of innovation. It's technically robust, yet its superpower is its business centricity. If you're involved in building IT and business strategies, it's essential to familiarize yourself with SAP BTP to see the big picture for digitalization with SAP solutions. Similarly, if you have design responsibilities for enterprise solutions, learning SAP BTP is crucial to produce effective and complete architecture designs. This book teaches you about SAP BTP in five parts. First, you'll see how SAP BTP is positioned in the intelligent enterprise. In the second part, you'll learn the foundational elements of SAP BTP and find out how it operates. The next part covers integration architecture guidelines, integration strategy considerations, and integration styles with SAP's integration technologies. Later, you'll learn how to use application development capabilities to extend enterprise solutions for innovation and agility. This part also includes digital experience and process automation capabilities. The last part covers how SAP BTP can facilitate data-to-value use cases to produce actionable business insights. By the end of this SAP book, you'll be able to architect solutions using SAP BTP to deliver high business value. What you will learn Explore value propositions and business processes enabled by SAP's Intelligent and Sustainable Enterprise Understand SAP BTP's foundational elements, such as commercial and account models Discover services that can be part of solution designs to fulfill non-functional requirements Get to grips with integration and extensibility services for building robust solutions Understand what SAP BTP offers for digital experience and process automation Explore data-to-value services that can help manage data and build analytics use cases Who this book is for This SAP guide is for technical architects, solutions architects, and enterprise architects working with SAP solutions to drive digital transformation and innovation with SAP BTP. Some IT background and an understanding of basic cloud concepts is assumed. Working knowledge of the SAP ecosystem will also be beneficial.